2021
DOI: 10.1007/s12325-021-01771-1
|View full text |Cite
|
Sign up to set email alerts
|

Citicoline and Vitamin B12 Eye Drops in Type 1 Diabetes: Results of a 36-Month Pilot Study Evaluating Macular Electrophysiological Changes

Abstract: Introduction: Our aim was to evaluate the effects of 36 months of treatment with citicoline and vitamin B 12 eye drops on macular function in patients with type 1 diabetes (DM1) with mild signs of non-proliferative diabetic retinopathy (NPDR). Methods: A prospective, randomized, interventional, monocentric, double-masked study was conducted. Twenty patients with DM1 were enrolled and randomly divided into two groups: the DC group (10 patients; mean age ± standard deviation 46.86 ± 8.78 years) in which one eye … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 38 publications
0
13
0
1
Order By: Relevance
“…In this regard, it has been demonstrated that treatment with eye drops containing citicoline and vitamin B12 for a 36month period improved the macular bioelectrical responses (multifocal electroretinography recordings) in type 1 diabetic patients (n ¼ 20) with nonproliferative diabetic retinopathy (NCT04009980). 94 The EUROCONDOR study is the largest study reported till now (n ¼ 449 patients) aimed at treating neurodegeneration. This phase II-III clinical trial provided evidence that 2 neuroprotective drugs (SST and brimonidine) administered by eye drops were able to arrest the progression of retinal neurodysfunction in type 2 diabetic patients.…”
Section: Clinical Trials and Perspectives In Humansmentioning
confidence: 99%
“…In this regard, it has been demonstrated that treatment with eye drops containing citicoline and vitamin B12 for a 36month period improved the macular bioelectrical responses (multifocal electroretinography recordings) in type 1 diabetic patients (n ¼ 20) with nonproliferative diabetic retinopathy (NCT04009980). 94 The EUROCONDOR study is the largest study reported till now (n ¼ 449 patients) aimed at treating neurodegeneration. This phase II-III clinical trial provided evidence that 2 neuroprotective drugs (SST and brimonidine) administered by eye drops were able to arrest the progression of retinal neurodysfunction in type 2 diabetic patients.…”
Section: Clinical Trials and Perspectives In Humansmentioning
confidence: 99%
“…As a neuromodulator, citicoline was shown to increase, in in vivo studies, the levels of neurotransmitters (dopamine, noradrenaline, and serotonin) in the central nervous system [ 8 ]. On the other hand, its neuroprotective properties were documented in in vitro models of neuroblastoma cells, dopaminergic mesencephalic neurons, on cultured retinal neurons, and in clinical studies on glaucoma and diabetic retinopathy [ 9 , 10 , 11 , 12 , 13 , 14 , 15 ]. Coenzyme Q 10 (Q10) is an endogenous lipophilic quinone, which exerts its functions within mitochondria, where it acts as an electron accepter, limits oxidative stress and inflammation, and prevents apoptosis [ 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…The use of topical citicoline combined with vitamin B-12 indicated a functional and morphological effect on retinal ganglion cells, presumably due to neuroenhancement, neuroprotection, and the neuroregeneration properties of citicoline. Patients under citicoline topical treatment preserved superficial and deep retinal vascular parameters on OCTA, indicating a potential protective effect on microvascular impairment over time [88,89]. More importantly, all these neuroprotective compounds are safe on a systemic profile with no potential interactions or side effects, except for ocular hyperemia as the most frequent local effect in the brimonidine group [78].…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 93%
“…Patients were followed at 12, 24, and 36 months performing 24-2 and 10-2 FDT, OCT with Spectralis mapping software, segmentation software, and OCT angiography to assess the superficial and deep vascular plexus. Adaptive optics was also performed sing Rtx1 (Imagine Eyes, Orsay, France) [88].…”
Section: Topical Citicolinementioning
confidence: 99%
See 1 more Smart Citation